2006
DOI: 10.1088/0022-3727/39/12/022
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of melt pool depth and dilution in laser powder deposition

Abstract: This paper presents a mathematical model of laser powder deposition (LPD) to predict temperature field, melt pool depth and dilution. The model validated by experiments is developed using the moving heat source method. In this method, the temperature distribution inside the clad and the substrate is obtained using the superposition principle and the solution of the heat diffusion due to a point heat source. The model, which can be used in real-time applications, predicts the melt pool depth and dilution as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(58 citation statements)
references
References 17 publications
0
56
0
2
Order By: Relevance
“…To confirm experimental correlations between melt-pool geometries and lateral menisci, an analytical model was developed, with an analytical description for every melt-pool, considering a similar approach than Fathi et al (2006). On a 2D cross section, each melt-pool was considered as the sum of two semi-ellipses x 2 /a 2 + y 2 /b 2 = 1 (one for the upper part, and one for the lower part).…”
Section: Analytical Description Of Surface Finishmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm experimental correlations between melt-pool geometries and lateral menisci, an analytical model was developed, with an analytical description for every melt-pool, considering a similar approach than Fathi et al (2006). On a 2D cross section, each melt-pool was considered as the sum of two semi-ellipses x 2 /a 2 + y 2 /b 2 = 1 (one for the upper part, and one for the lower part).…”
Section: Analytical Description Of Surface Finishmentioning
confidence: 99%
“…All these factors influence the thermal history T = f(x, y, z, t) of the part, and contribute not only to the melt-pool shapes, and the resulting layer growth, but also to the final metallurgical and mechanical properties Recently (2006Recently ( -2011, intensive numerical work has been carried out to model the DMD process, starting from the laser-powder interaction, to the thermo-mechanical calculation of residual stresses, including or-not metallurgical aspects. Authors like Fathi et al (2006) proposed rather simplified predictive models to predict the geometrical characteristics of the walls by assuming a solid state during the process. Whereas, more complex thermohydraulic calculations considered free moving surfaces, either on 2D multilayers configurations like Morville et al (2011), or on 3D single layer as shown by Qi et al (2006) or Kumar and Roy (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Various numerical or analytical models have also addressed the formation of wall geometries by considering either element activation including a time discretization of the process, 5,6 predefined analytical function of the final shape like those by Pinkerton and Li 7 or Fathi et al, 8 or a more physical self-consistent displacement of the free surface including the powder feed distribution in the velocity 2,9,10 with the use of a level-set method. However, except in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Control of these characteristics requires a good understanding of the relationship between the independent process variables, such as laser power, beam parameters, transverse speed, powder feeding rate shielding gas speed, and the deposit properties such as track geometry, mechanical properties, surface roughness, and microstructure. Several authors have attempted to make the link via analytical [7], numerical or empirical means [8]. However, most of these studies considered the melt pool as quasi-stationary and thus do not consider factors that caused or resulted from pool instability.…”
Section: Introductionmentioning
confidence: 99%